Educação permanente em saúde para assistência a adultos com hipertensão arterial: revisão de escopo - Uhatela, Wilsa Kaina Managem Fernandes (2024)
Objective: to characterize studies on continuing health education in assisting adults with hypertension. Method: consists of a scoping review, initiated with the development of a protocol, using the Joanna Briggs Institute guidelines as a basis and registered on the Open Science Framework platform. The review question was: how has permanent health education been characterized in health care for adults with Hypertension? Primary studies, with qualitative, quantitative or mixed approaches, in any language were included. The exclusion criteria were studies that did not meet the objective of the review and those that were incomplete/unavailable in the databases. No time frame was established. The search was carried out in data sources Medline/Pubmed, Scopus and LIlacs, from July to October 2023. To manage references, Mendeley software was used. The data was subjected to coding and content analysis. The sample consisted of 13 articles, predominantly published in English and Portuguese in the period from 1985 to 2021. The studies were developed in Brazil, mainly, the United States of America, France and Italy. The predominant scenario was Primary Health Care. The majority of participants involved were the nursing team and doctors. The topics covered in the studies were the technique for checking blood pressure, evaluation of hypertension programs, evaluation of educational processes for the conduct of professionals with patients with the disease. It is considered that there is little research that addresses continuing education with the topic of Arterial Hypertension, as it is a relevant strategy for teachingservice integration and has the potential for significant learning in the Unified Health System.